Exploring possibilities of Islamic tourism in Malaysia - M Noor Azman, Nor Afifin Nadia; Zulkifle, Nur Najwa; Md Sawari, Siti Salwa (Kulliyyah of Languages and Management, International Islamic University Malaysia, 2019)
Malaysia is one of the country that rich in diversities, heritages and cultures, however, it is clearly declared that the official religion of the country is Islam. The fact, Islam is the official religion makes it easier to market Malaysia as an Islamic tourism destination. This research paper aims to analyses the current trends and opportunities of Islamic Tourism industry in Malaysia. A document analysis was initially employed to identify the objectives of this research paper. The results of the study have shown the current trends of some travel agents and service providers who have creatively came out with Muslim-friendly packages and tours to attract and gain the attention of Muslim travellers. Besides that, the results of this study have determined three major opportunities of Islamic tourism in Malaysia which are halal holidays, halal tourism smart phone apps and promotions. The futuristic elements of this paper are aimed to promote Islamic products that can be further developed in terms of its quality of production, the benefit of decision-making among Islamic countries, and the ability to raise the dignity of Islam in the eyes of the world.